Exploring nursing interventions in family-based approaches for preventing bullying among children and adolescents : a scoping review - Iyus, Yosep; Ai, Mardhiyah; Helmy, Hazmi; Rohman, Hikmat (BioMed Central Ltd., 2025)
Background Bullying is a prevalent issue faced by children and adolescents in both school and community settings. One contributing factor to bullying behavior is the limited involvement or inadequate role of the family in addressing this issue. However, there is a noticeable gap in existing research regarding nursing interventions that focus on family-centered approaches to prevent bullying. Identifying and analyzing these interventions is crucial to enhancing the role of families in reducing bullying behavior. The aim of this study is to explore and map the various nursing-led, family-based interventions designed to mitigate bullying among children and adolescents, and thereby addressing this critical scientific gap. Methods This study employed a scoping review method following Arksey and O’Malley’s framework, including identifying research questions, systematically searching CINAHL, PubMed, and Scopus. The databases used are CINAHL, PubMed, and Scopus. The major keywords used are parenting, family interventions, bullying, adolescents, and children. Inclusion criteria in article selection were family-based intervention, English language, full-text, original research, and publication period in the last 15 years (2010-2024). Data analysis was carried out descriptively qualitatively. Results The results of this research show that there are 10 articles that discuss Interventions focused on Family to reduce bullying behavior in children and adolescents. Various types of Interventions focused on Family are effective in reducing bullying behavior in children and adolescents, including improving parenting patterns, family-based education, and collaboration between school and family (p value<0.05). Some of the activities carried out are education, role play, counseling, managing conflict, and conducting assessments. Interventions can be carried out offline and online. Interventions focused on Family offer a holistic and sustainable approach to dealing with bullying behavior in children and adolescents. The advantages of this intervention include improving family relationships, strengthening communication skills, and better understanding of children’s emotions.